A Discursive Analysis of Power Relationships in the “ One Piece” Anime Series: The Sabaody Archipelago Arc Search for Theoretical Perspectives in the Sir Journal - Silva Putri Monica Loupatty; Fabianus Fensi (International Journal Labs, 2026)
This study examines the representation of power relations in the One Piece anime series, particularly in the Sabaody Archipelago Arc. The background of this research is based on the growing significance of anime as a global popular culture product that not only functions as entertainment but also represents social inequality, domination, and resistance. The purpose of this study is to analyze how power relations are constructed, maintained, and normalized through discourse, dialogue, and narrative interaction between characters. This research uses a qualitative approach with Michel Foucault’s discourse analysis as the main theoretical framework. The data were collected through documentation by observing selected episodes of the Sabaody Archipelago Arc, transcribing relevant dialogues, and identifying scenes that represent power relations. The findings show that power in this arc operates through five main dimensions: power relations in statements, language as a tool of power, normalization of social relations, panopticon mechanisms in statements, and marginalized subjects. The domination of the Tenryuubito is not only shown through physical violence but also through verbal authority, social fear, and internalized obedience among subordinate groups. This study concludes that the Sabaody Archipelago Arc functions as a critical media text that reveals how discourse can reproduce hierarchy, legitimize domination, and normalize social inequality.